Effects of crude methanol extract of Euphorbia hirta on Hematological and Biochemical indices and histological changes of liver in African Catfish Clarias gariepinus (Burchell, 1822). - Sheikhlar, A.R; Alimon, Abdul Razak; Mohd. Daud, Hassan; Saad, Che Roos; Fard, E. Ramezani (Academic Journals, 2011)
Methanol extract of Euphorbia hirta was tested in in vivo experiment to investigate the effect on hematological and biochemical indices and histological changes of liver in the African catfish (Clarias gariepinus). The plant methanol extract was included in the feed and administered to the fish. The experiment was conducted for eight weeks and with five diets including control (E. hirta-0), 2 (E. hirta-2), 5(E. hirta-5), 7(E. hirta-7) and 9(E. hirta-9) g E. hirta kg-1 of dry matter diet. Fish fed the E. hirta-9 diet had lowest (p<0.05) RBC and TP compared with the other dietary groups. Histological analyses revealed this group (E. hirta-9) had histopathologic alterations in the liver. Results of this study indicated that methanol extract of E.hirta by 7 g kg-1 can be safely used to improve hematological indices of African catfish without any adverse effect on the liver.